PERAN INTEGRATIF PENDIDIKAN JESUIT DALAM FORMASI KEPEMIMPINAN IGNATIAN - Witono, Odemus Bei (Sanata Dharma University, 2024)
This article explores through a qualitative approach the guiding principles and educational philosophy of Jesuit institutions, focusing on their holistic approach to personal and intellectual development. Key elements include the integration of faith and reason, the commitment to social justice, and the formation of students as conscientious and competent leaders. Central to this philosophy are the concepts of finding God in all things, the transience and immanence of God, and the dedication to the greater glory of God (AMDG) and the principle of